FTIR imaging of brain tissue reveals crystalline creatine deposits are an ex vivo marker of localized ischemia during murine cerebral malaria: General implications for disease neurochemistry - Hackett, Mark; Lee, J.; El-Assaad, F.; McQuillan, J.; Carter, E.; Grau, G.; Hunt, N.; Lay, P. (American Chemical Society, 2012)
Phosphocreatine is a major cellular source of high energy phosphates, which is crucial to maintain cell viability under conditions of impaired metabolic states, such as decreased oxygen and energy availability (i.e., ischemia). Many methods exist for the bulk analysis of phosphocreatine and its dephosphorylated product creatine; however, no method exists to image the distribution of creatine or phosphocreatine at the cellular level. In this study, Fourier transform infrared (FTIR) spectroscopic imaging has revealed the ex vivo development of creatine microdeposits in situ in the brain region most affected by the disease, the cerebellum of cerebral malaria (CM) diseased mice; however, such deposits were also observed at significantly lower levels in the brains of control mice and mice with severe malaria. In addition, the number of deposits was observed to increase in a time-dependent manner during dehydration post tissue cutting. This challenges the hypotheses in recent reports of FTIR spectroscopic imaging where creatine microdeposits found in situ within thin sections from epileptic, Alzheimer's (AD), and amlyoid lateral sclerosis (ALS) diseased brains were proposed to be disease specific markers and/or postulated to contribute to the brain pathogenesis. As such, a detailed investigation was undertaken, which has established that the creatine microdeposits exist as the highly soluble HCl salt or zwitterion and are an ex-vivo tissue processing artifact and, hence, have no effect on disease pathogenesis. They occur as a result of creatine crystallization during dehydration (i.e., air-drying) of thin sections of brain tissue. As ischemia and decreased aerobic (oxidative metabolism) are common to many brain disorders, regions of elevated creatine-to-phosphocreatine ratio are likely to promote crystal formation during tissue dehydration (due to the lower water solubility of creatine relative to phosphocreatine). The results of this study have demonstrated that although the deposits do not occur in vivo, and do not directly play any role in disease pathogenesis, increased levels of creatine deposits within air-dried tissue sections serve as a highly valuable marker for the identification of tissue regions with an altered metabolic status. In this study, the location of crystalline creatine deposits were used to identify whether an altered metabolic state exists within the molecular and granular layers of the cerebellum during CM, which complements the recent discovery of decreased oxygen availability in the brain during this disease. © 2012 American Chemical Society.